2021
DOI: 10.1177/11795514211030513
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical Experience on the Usage of High-Dose Metformin (1500-2500 mg/day) in Type 2 Diabetes Management

Abstract: Background: To evaluate the clinical characteristics, treatment patterns, and clinical effectiveness and safety of high doses of metformin (1500-2500 mg/day) in Indian adults with type 2 diabetes mellitus (T2DM). Materials and methods: A retrospective, multicentric (n = 241), real-world study included patients with T2DM (aged >18 years) receiving high doses of metformin. Details were retrieved from patient’s medical records. Results: Out of 5695 patients, 62.7% were men with median age was 50.0 years. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…24 Furthermore, in a real-world study across 241 centres in India (n = 5695), metformin therapy reduced HbA1c from 67 to 55 mmol/mol, with a mean change from baseline of 12 mmol/mol. 25 Although a direct comparison between Asian and non-Asian T2D subjects on metformin monotherapy is still lacking, these recent results support consistent efficacy across ethnic/racial groups.…”
Section: Ethnicity and Racementioning
confidence: 86%
See 1 more Smart Citation
“…24 Furthermore, in a real-world study across 241 centres in India (n = 5695), metformin therapy reduced HbA1c from 67 to 55 mmol/mol, with a mean change from baseline of 12 mmol/mol. 25 Although a direct comparison between Asian and non-Asian T2D subjects on metformin monotherapy is still lacking, these recent results support consistent efficacy across ethnic/racial groups.…”
Section: Ethnicity and Racementioning
confidence: 86%
“…Yet, among 5503 Asians (75% Chinese) followed in a primary care setting, metformin monotherapy induced an absolute reduction in HbA1c of approximately 5, 11 and 22 mmol/mol in PwD with progressively greater baseline HbA1c levels of 53–64 mmol/mol, 64–75 mmol/mol, or above 75 mmol/mol, respectively 24 . Furthermore, in a real‐world study across 241 centres in India ( n = 5695), metformin therapy reduced HbA1c from 67 to 55 mmol/mol, with a mean change from baseline of 12 mmol/mol 25 . Although a direct comparison between Asian and non‐Asian T2D subjects on metformin monotherapy is still lacking, these recent results support consistent efficacy across ethnic/racial groups.…”
Section: Glucose‐lowering Efficacy In Distinct Patient Populationsmentioning
confidence: 96%
“…In Saudi Arabian hospitals, metformin is usually prescribed for both newly diagnosed and long-term diabetes patients. 17 A recent retrospective study done in the Kingdom of Saudi Arabia by Al-Rubeaan et al reported that among 519 Saudi type 2 diabetics 89.2% were prescribed metformin as the first line of treatment which shows that the majority of physicians still consider metformin as the best option in diabetes management. 18 Various meta-analyses and systemic reviews have described metformin's role in glycemic control shown by reduced HbA1c levels by an average of 1 to 2% in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…MET has multiple activities and excellent therapeutic efficacy in different pathological environments (Das et al, 2021;Drzewoski and Hanefeld, 2021;Rajgopal and Kochhar, 2021). However, most patients under long-term MET treatment (>10 years) have poor blood glucose control (Cherney and Lam, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits anti-diabetic effects by changing gut microbial communities ( Cherney and Lam, 2018 ; Guo and Xie, 2018 ; Sun et al, 2018 ; Vallianou et al, 2019 ). MET has multiple activities and excellent therapeutic efficacy in different pathological environments ( Das et al, 2021 ; Drzewoski and Hanefeld, 2021 ; Rajgopal and Kochhar, 2021 ). However, most patients under long-term MET treatment (>10 years) have poor blood glucose control ( Cherney and Lam, 2018 ).…”
Section: Introductionmentioning
confidence: 99%